Engineering All‐Purpose Amorphous Carbon Nanotubes with High N/O‐Co‐Doping Content to Bridge the Alkali‐Ion Batteries and Li Metal Batteries. Issue 14 (18th March 2021) - Zhang, Xiao‐Hua; Jiang, Ru; Fan, Chao‐Ying; Xie, Dan; Li, Bao; Zhang, Jing‐Ping; Wu, Xing‐Long
Abstract: All‐purpose electrode materials (APEMs), which can be effectively available on not only alkali‐ion batteries but also emerging Li metal batteries, are urgently pursued to open up cost‐efficient tactics for practical application of energy storage systems (ESSs), but still remain challenging. Herein, the hierarchical porous carbon nanotubes network (NOPCT) with well‐tailored nanoarchitecture and high N/O‐co‐doping content (20.6 at%) is developed to present large‐span application on ESSs. As for Li/Na‐ion batteries, the NOPCT delivered excellent cycle stability and robust rate performance in a conventional ester‐based electrolyte. Moreover, NOPCT also serving as a metal Li host can effectively guide smooth and uniform Li nucleation/growth to enhance the cycle stability of hybrid Li metal anodes. In addition, the NOPCT played an important role in the sustainability of sulfur electrodes, promising the feasibility of shared NOPCT for practical Li–S batteries. First‐principle calculations demonstrate that graphitic‐N and CO function groups favor for improving electron conductivity while the pyridinic‐N and CO function group make sense for improved Li/Na adsorption and affinity through Lewis acid‐base interaction, enlightening the interplay between various doped categories on improved electrochemical performance of NOPCT. This work provides profound theoretical and experimental insight into the design and development of APEMs for advanced ESSs. Abstract : An all‐purpose electrode material (APEM) composed of amorphous carbon nanotubes with high N/O‐co‐doping content (NOPCT) is prepared. NOPCT can deliver outstanding behaviors in cycle and rate capability for Li/Na‐ion batteries, Li nucleation/growth serving as host of Li anode, and suppressing shuttle effect of Li polysulfides in Li–S batteries. It provides a profound insight into the design of APEM.